Central Odontogenic Myxoma: A Radiographic Analysis - Ahmad Badruddin Ghazali; Raweewan Arayasantiparb; Rachai Juengsomjit; Aroonwan Lam-ubol (Hindawi Limited, 2021)
Objective. This study aimed to determine the radiographic characteristics of odontogenic myxomas (OMs) and their associations. Materials and Methods. The study enrolled radiographs of patients taken between 2005 and 2019 with a confirmed histopathological diagnosis of central OM. OM radiographic features were evaluated, including location, border, locularity, involved area, the number of included teeth, root resorption, tooth displacement, bone expansion, bone perforation, and periosteal reaction. Fisher's exact test was used for statistical analysis. Results. Significant associations were found between the OM border and the affected jaw (p=0.036), locularity (p=0.036), involved areas (p=0.009), and bone perforation (p=0.036). OMs with an ill-defined border were associated with maxillary lesions, multilocularity, dentate areas, and cortical bone perforation. The number of included teeth (2 or fewer or 3 or more) was significantly associated with locularity (p=0.010), involved area (p=0.045), and bone expansion (p=0.010). Larger OMs including 3 or more teeth, were associated with a multilocular appearance, dentate areas, and bone expansion. Conclusion. The border of OM and the number of included teeth are related to other radiographic appearances. Understanding these relationships could help in treatment decisions and help better understand the nature of OM.